Does Vibrissal Innervation Patterns and Investment Predict Hydrodynamic Trail Following Behavior of Harbor Seals (Phoca vitulina)?. Issue 10 (3rd May 2019) - Jones, Aubree; Marshall, Christopher D.
ABSTRACT: Our understanding of vibrissal function in pinnipeds is poor due to the lack of comparative morphological, neurobiological, and psychophysical performance data. In contrast, the function of terrestrial mammalian vibrissae is better studied. Pinnipeds have the largest vibrissae of all mammals, and phocids may have the most modified vibrissae. The tactile performance for pinniped vibrissae is well known for harbor seals ( Phoca vitulina ). Harbor seals display at least two types of tactile behavior involving their mystacial vibrissae: a fine discriminatory capability using active touch and hydrodynamic trail following (the ability to detect and follow turbulent trails). This study investigated innervation patterns of harbor seal follicle‐sinus complexes (F‐SCs) to test the hypothesis that the whiskers used in hydrodynamic trail following possess increased innervation investment compared to other phocids. Therefore, the most lateral vibrissae from five harbor seals were histologically processed so that morphometric measurements and axon counts could be collected. Vibrissae from one harbor seal were immunolabeled with anti‐protein gene product (PGP 9.5) to document the pattern of deep vibrissal nerve innervation of the F‐SCs. Overall, harbor seals showed an innervation pattern (axons/F‐SC and axons/muzzle) similar to other phocids. The ventrolateral vibrissae, involved in hydrodynamic trail following, have greater axon density in harbor seals than harp seals, suggesting harbor seal F‐SC innervation patterns could explain their performance at trail following. The combination of microstructural, innervation investment, and behavioral data provides a foundation for functional inference regarding this tactile behavior in harbor seals and also facilitates future comparative work for other pinniped species. Anat Rec, 302:1837–1845, 2019. © 2019 American Association for Anatomy